The repercussions of the phenomenon of extremism in Iraq after 2014 and how to address it - noor mushtaq hasen (Tikrit Journal For Political Science, 2025)
wnzraan lizahirat altataruf baed tahadiy jadid lilmujtamae eam 2003m hataa zaezaeat tajsidiat waminat lilbasar, walakina aldawlat ealaa jamie almustawayat sawa' kan ealaa mustawaa al'aman walsiyasii walmujtamaeii walaiqtisadii, adha an muajahat altataruf hu wade astiratijiat tatabanaa tabaniy wanahj jadid wamasarat 'iislahiatan bialnazar 'iilaa hadhih alzaahirat wanazrat almujtamae minha.